A flawed trial - Abd Razak, Dzulkifli (2007)
Metaphorically speaking, the head of the person who "tried to kill my dad" was finally handed to the US president. For all of Saddam Hussein haters, at least momentarily, there was a feeling of relief, if not triumph. In the words of the Iraqi deputy foreign minister: "The people of Iraq are the victors in the issue of Saddam's hanging, just as they were the main victors in his fall." Though this may appear as an overstatement, it did display the deep sentiments involved. Otherwise, how else would one explain the disregard for the timing of the execution held during the feast of Aidiladha, regarded as a time for compassion and forgiveness.